INDUSTRI MIKRO DAN KECIL: PERAN TERHADAP PEREKONOMIAN DAERAH DAN PENYERAPAN TENAGA KERJA - Hasna Noor Alifa; Enggar Bayu Kusumaningrum; Dhiya Putri Maharani (Fakultas Ekonomi Universitas IBA Palembang, 2021)
This study aims to examine the role of the number of units and the output value of small medium enterprise on the regional economy and employment in the provinces in Indonesia in 2017-2019. The dependent variable used is the regional economy and employment, while the independent variable is the number of units and the output value of small medium enterprise. This study uses secondary data with panel data regression analysis techniques. The number of samples used were 34 samples with a total sample of 102 observations. The panel data regression model used in this study is the Fixed Effect Model. The results showed that the variable number of industrial units and output value had no effect on the dependent variable of the regional economy. However, the number of industrial units and the output value have a positive effect on the dependent variable of employment.